Analysis of precision and accuracy of Precipitable Water Vapour derived from GPS observations - IGONDOVÁ, Miroslava (Contributions to Geophysics and Geodesy, 2009)
A  Precipitable Water  Vapour (PWV ),  one  of the  parameters deﬁning  an instant state of troposphere, can  be derived from  the  combination of GPS observations and  ground  meteorological measurements.  The precision  of the PWV values depends  on many  variables used  in the computation. Their  inﬂuence  is discussed and  analysed. The accuracy of the  GPS  based  PWV  values is estimated by  comparison to the  radiosonde based  PWV values within  the period  2004–2007.  Due to diﬀerent  behaviour of the PWV with  respect to time of the year,  the analysis is performed in each  season  separately.